Antioxidant and Antibacterial Activity of Extract Combination from Sonneratia alba and Heterotrigona itama Propolis - Amilia, Andini Nur; Kustiawan, Paula Mariana (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Sonneratia alba or rambai leaves are a plant from East Kalimantan that the community has used for generations as a cold powder. Antioxidants are needed to ward off free radicals, while bacteria are one of the causes of acne. Propolis also shows potential as an antioxidant and antibacterial agent. This research evaluated whether the combination of Sonneratia alba leaves extract and Heterotrigona itama propolis can increase antioxidant and antibacterial activity and whether this combination has synergistic potential. The S. alba leaves and H. itama propolis were macerated using ethanol as the solvent. The antioxidant activity test using the DPPH method with three comparisons of 1:1, 1:2, and 2:1 produced IC50 values of 12.669 µg/ml, 32.756 µg/ml, and 19.694 µg/ml, respectively. The IC50 value for ascorbic acid is 12.293 µg/ml. The results show that the combination of S. alba leaves and H. itama propolis ethanol extract has very strong antioxidant activity. The antibacterial activity test against Staphylococcus aureus bacteria with three concentrations of 60%, 80%, and 100% showed inhibition zones of 10.5 mm (medium category), 16 mm, and 17.5 mm (strong category), respectively.